2013
DOI: 10.5194/acp-13-4707-2013
|View full text |Cite
|
Sign up to set email alerts
|

Source attributions of pollution to the Western Arctic during the NASA ARCTAS field campaign

Abstract: We use the NASA GEOS-5 transport model with tagged tracers to investigate the contributions of different regional sources of CO and black carbon (BC) to their concentrations in the Western Arctic (i.e., 50–90° N and 190–320° E) in spring and summer 2008. The model is evaluated by comparing the results with airborne measurements of CO and BC from the NASA Arctic Research of the Composition of the Troposphere from Aircraft and Satellites (ARCTAS) field campaigns to demonstrate the strengths and limitations of ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
91
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 69 publications
8
91
0
Order By: Relevance
“…Bian et al (2013) demonstrated that the ARCTAS measurements along the flight track were representative of regional averages during spring 2008. Figure 6 shows the in situ extinction profiles observed during the April 2008 ARCTAS deployment over the AK region.…”
Section: Arctas Aircraft Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bian et al (2013) demonstrated that the ARCTAS measurements along the flight track were representative of regional averages during spring 2008. Figure 6 shows the in situ extinction profiles observed during the April 2008 ARCTAS deployment over the AK region.…”
Section: Arctas Aircraft Measurementsmentioning
confidence: 99%
“…The summer 2008 IPY measurements showed that the East Asian contribution to Arctic CO and aerosols was small, indicating inefficient transport as well as enhanced wet scavenging of aerosols (Matsui et al, 2011;Bian et al, 2013). Despite high plume dilution and stronger wet removal in summer, several aerosol plumes were traced to both fossil-fuel and biomass burning origins, and all showed a preponderant component of highly oxygenated organic carbon compounds (> 70 %) with relatively larger sulfate fractions for plumes originating in industrialized regions (Schmale et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are number of factors including but not limited to the uncertainties in emissions, and the complicated transport pathways from mid-latitudes to the Arctic that contribute to the uncertainties in calculating the impacts of emission sources (Bian et al, 2013;Fuelberg et al, 2010).…”
mentioning
confidence: 99%
“…Shindell and Faluvegi, 2009;Flanner, 2013;Sand et al, 2013) indicated that a 25 significant part (up to about 50 %) of this temperature increase could have been induced by BC. There is abundant evidence that BB provides a significant contribution to BC in the Arctic atmosphere in the spring and summer (e.g., Stohl, 2006;Stohl et al, 2006;Warneke et al, 2010;Bian et al, 2013). It was also estimated that Siberian fires alone contributed almost half (46 %) of the total BC amount deposited in the Arctic over a period of 12 years (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013).…”
Section: Introductionmentioning
confidence: 99%